Influence of Humic Acid Colloid on Adsorption of Oxytetracycline in Sediment - Gao1, Lunchuan; Yang1, Shengke; Wang1, Di; Gao1, Chanjuan; Wang1, Geng (Asian Journal of Chemistry, 2014)
Oscillating balance method was employed to study the adsorption of oxytetracycline (OTC) in sediment and its kinetic and thermodynamic properties with the presence of humic acid colloid (HA). The results showed that the equilibrium time of the adsorption of oxytetracycline in sediment with the existence of humic acid colloid was 12 h, while it was 24 h without humic acid colloid , which indicated that humic acid colloid can accelerate the adsorption of oxytetracycline in sediment. The adsorption kinetics was found to follow the pseudo first-order kinetics model. Langmuir and Freundlich model can preferably describe the isothermal adsorption process of oxytetracycline in sediment under different concentrations of humic acid colloid. But Langmuir model fitted better and four kinds of error function values were smaller. Thermodynamics results showed that the adsorption of oxytetracycline in sediment was spontaneous, endothermic and entropy-increasing. The value of DG° of adsorption process remained negative with humic acid colloid , but the absolute value decreased, indicating that it tended to physical adsorption. When adding humic acid colloid , the initial pH value greatly affected the adsorption of oxytetracycline in sediment. The adsorption quantity of oxytetracycline increased with the increase of pH when pH was 3-6, remained at a higher level when pH was 6-9 and decreased slightly when pH was greater than 9.